Science in the Kitchen : A Scientific Treatise On Food Substances and Their Dietetic Properties, Together with a Practical Explanation of the Principles of Healthful Cookery, and a Large Number of Original, Palatable, and Wholesome Recipes - Kellogg, E. E. (Ella Ervilla), 1853-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"Science in the Kitchen" by E. E. Kellogg is a scientific treatise that was written during the late 19th century. This work delves into the art and science of dietary practices, exploring the relationship between food preparation, health, and nutrition. The book likely covers principles of healthful cookery, backed by scientific principles, and gives numerous recipes aimed at providing wholesome and nourishing meals. The opening portion of the text sets the stage for an exploration of how modern science can transform traditional cooking methods. It discusses the increasing interest in scientific cookery and dietetics, as reflected in the establishment of cooking schools. The author highlights the inadequacies of conventional methods and emphasizes a systematic approach to the preparation of food, aiming for simplicity and nutritional value. Mrs. Kellogg outlines the need for a scientific understanding of food along with practical advice on cooking and dietary combinations, indicating a shift from mere culinary skill to informed, health-oriented practices. (This is an automatically generated summary.)
Release date is 2004-05-01
E-text prepared by Charles Franks, Stephen Schulze, and the Project Gutenberg Distributed Proofreading Team from digital images provided by Michigan State University Libraries
Keywords: Cooking, American; Diet; Vegetarianism